WHY PRODESKEL IMPLEMENTATION VARIES: A COLLABORATIVE GOVERNANCE ANALYSIS OF VILLAGE DIGITAL DATA MANAGEMENT IN GIRI, BANYUWANGI - Dirhan Eka Pradipta; Amy Yayuk Sri Rahayu (Journal of Social Politics and Governance (JSPG), 2026)
This study examines why the implementation of the Village and Sub-District Profile Information System (Prodeskel) produces uneven outcomes across local settings in Giri, Banyuwangi, Indonesia. The research problem lies in the persistence of administrative, institutional, and participatory constraints despite the formal availability of a digital village information system. This study aims to analyze how collaborative governance shapes the implementation of Prodeskel and to identify the factors that determine its effectiveness at the local level. The analysis is grounded in the collaborative governance ansel and gash (2008) framework, particularly the dimensions of starting conditions, institutional design, facilitative leadership, and collaborative process. This research employed a qualitative comparative case study approach using interviews, document review, and thematic analysis. The findings show that the implementation of Prodeskel is influenced not only by technical capacity but also by the quality of leadership, institutional clarity, inter-actor trust, and the degree of community participation. Villages and sub-district actors with stronger facilitative leadership and clearer coordination mechanisms demonstrate more consistent data updating and better implementation outcomes. This study recommends strengthening institutional coordination, improving local technical capacity, and expanding participatory mechanisms to support inclusive and sustainable village digital governance.